The Impact of Macroeconomics and the Covid-19 Pandemic on the Sustainability of Agribusiness Companies in Indonesia - Sianturi, Elisa Yemina; Feryanto, Feryanto (The Indonesian Forestry Certification Cooperation, 2023)
The Covid -19 pandemic and changes in macroeconomic conditions have had an impact on the performance and sustainability of companies around the world, including in Indonesia. This study analyzes the effects macroeconomic changes and the pandemic have on corporate performance and sustainability, proxied by stock prices. Five macroeconomic variables i.e. inflation, exchange rate, BI interest rate, world oil price, and palm oil price are used as the independent variables, the COVID-19 pandemic as a dummy variable and agribusiness company stock prices as the dependent variable. The data used is secondary data from 2015 to 2020 and analyzed by the ECM (Error Correction Model). The results show that in the short-run, world oil prices and palm oil prices affect upstream agribusiness companies’ share prices, while for the downstream companies, all variables including the COVID-19 pandemic have no effect on share price performance. In the long-run, however, all variables including the COVID-19 pandemic statistically affect upstream companies’ share price performance, while for the downstream companies, all variables but BI interest rate affect share price performance.